G511(P) The trends and geographical variations in place of deaths in children and young people with cancer: Population-based study in England 1993–2013. (27th April 2016) - Gao, W; Verne, J; Peacock, J; Stiller, C; Wells, C; Greenough, A; Higginson, IJ
Abstract : Objectives: To examine the trend and geographical variation in place of death (PoD) for children and young people (CYP) who died with cancer and factors associated with these variations, in the context of a series of national initiatives for end of life care (EoLC) improvement in adults since late 1990s. Design and setting: Population-based cross-sectional study in National Health Service (NHS) England. Data and methods: Death records of CYPs (≤24 years) who died with cancer (N=12, 242) in England, 1993–2013. Main outcome measures time trends in proportions of deaths in hospitals, home or hospices, using Tobit regression analysis; and proportion ratio (PR, 95% confidence interval) of the factors independently associated with the PoD, derived from modified Poisson regression models. Results: Cancer accounted for 19% of all CYP deaths from non-external causes, among which one third were haematological cancer. 49% of the deaths occurred in hospitals, 40% at home and 9% in hospices. Hospital deaths reduced from over 50% to 44%(95% CI: 43–46%); hospice deaths increased from under 10% to 13% (95% CI: 12–14%); home deaths fluctuated at around 40%. Children were more likely to die in home than young adults (PRs 1.23–1.62); those who died from haematological cancer (vs brain and CNS tumours) or with more contributing CoDs were less likely to die at home (PRs 0.18–0.75) or in hospice (PRs 0.04–0.38); those living in areas with higher deprivation were less likely to die at home. The PoD varied considerably by geographical region (P < 0.005), the variability widened for home death (PRs vs London 0.86–1.42 and 1.05–1.44) and narrowed for hospice death (PRs 0.52–3.44 and 0.94–1.87), in 1993–2000 and 2005–2013, respectively. Conclusion: Home and hospice become increasingly important for children and young people with cancer spending their last moments of life, suggesting more support is needed in both settings. The persistent high hospital death in haematological cancer and in patients with comorbid conditions, highlights the importance of developing in-hospital palliative care facilities and enhancing care capacities in home and hospices to manage these cases; the deprivation-related inequalities and the wide geographical variation in PoD warrant further investigation and may need policy-level intervention.